Staphylococcus aureus characterization in commercial rabbit farms reveals high genetic diversity and widespread antimicrobial resistance - Mascarós, Patricia; Martínez-Seijas, Carmen; Díaz-Méndez, José Francisco; Rosell Pujol, Juan María; Sanz, Celia; Arnau-Bonachera, Alberto; Selva, Laura; Corpa, Juan M.; Viana, David (Frontiers in Veterinary Science, 2025)
Staphylococcus aureus is a relevant bacterium in animals and a major public health concern, recognized by the World Health Organization as a priority pathogen due to its critical role in antimicrobial resistance. In rabbits, it is a leading cause of mastitis, pododermatitis, and abscesses, and the primary cause of culling in reproductive does. However, its genetic diversity, transmission dynamics, and resistance patterns in this context remain poorly understood. This study aimed to characterize the genetic structure, geographical dissemination, and antimicrobial resistance profiles of S. aureus isolates from rabbit farms across the Iberian Peninsula. A sampling strategy based on the official farm census ensured representativeness. Sequencing and epidemiological data were used to assess clonal lineages and distribution, and antimicrobial resistance was also evaluated. The results revealed high clonal diversity, including 10 clonal complexes (CCs) and 35 sequence types, with 18 previously unreported in rabbits. However, this diversity was largely dominated by two lineages, CC121 and CC96, which together account for nearly 90% of all isolates. Geographical proximity and commerce influenced strain distribution, with defined patterns for certain lineages. Resistance was observed against all 14 tested antibiotics, including key classes for human medicine: cephalosporins, oxazolidinones, and glycylcyclines. Notably, 86.1% of isolates were classified as multidrug-resistant (MDR), and 9.1% were methicillin-resistant (MRSA). This study provides the most comprehensive and representative characterization to date of S. aureus diversity, dissemination patterns, and antimicrobial resistance in rabbit farming, underscoring the importance of continuous surveillance and reinforcing the need for improved control strategies and preventive measures within a One Health framework. To support the rabbit industry, we have developed “StaphyMAP,” an open-access, interactive platform that provides anonymized, real-time data on the distribution, genetic diversity, and antimicrobial resistance patterns of Staphylococcus aureus isolates. This tool aims to assist veterinary clinicians in making informed empirical treatment decisions, thereby promoting more rational antimicrobial use and helping to curb the overuse of broad-spectrum antibiotics.